A case of female urogenital schistosomiasis presenting as viral warts. (July 2015) - Samuel, MI; Taylor, C
Schistosomiasis is uncommon in the UK but is found in migrant populations and in those who travel to areas of endemic schistosomiasis. Apparent clinical symptoms may occur long after the patient has left an endemic area. Female urogenital schistosomiasis (arising from infection by Schistosoma haematobium, endemic in Africa and the Middle East) may show a variety of lesions in the female genital tract, some of which may be misdiagnosed as viral warts. One such case is presented here. A young woman presented with lesions on the labia minora suspected to be viral warts which had not responded to treatment with cryotherapy. Biopsy of the lesions and spun urine microscopy revealed S. haematobium eggs. The lesions resolved following treatment with praziquantel. Clinicians should also be aware of the high rate of urogenital schistosomiasis in women from endemic areas, which is associated with urogynaecological morbidity and also increases the risk of acquisition of HIV infection.